CONTENT, FORM AND METHODS OF USING INNOVATIVE TECHNOLOGIES IN THE EFFECTIVE ORGANIZATION OF EDUCATIONAL CLASSES (American Journal of Technology and Applied Sciences, 2023)
Categories of purpose, content, form reveal the essence of the educational process (what it is aimed at, what it fills, what it is directed at, in what form it is completed). However, there is also another important category related to the question of how to educate in highlighting the essence of upbringing. This is a concept of the method of upbringing.